동위원소-안정화된 테트론이미드 화합물 - SEERDEN JEAN PAUL; OLSEN MARK JON (2021)
하나 이상의 중수소 원자를 포함하는 동위원소-안정화된 테트론이미드 화합물, 이의 유도체 및 중간체, 이들의 합성 방법, 이의 약제학적 조성물, 및 무세포(cell-free) 샘플, 세포- 및 조직-기반 검정, 동물 모델 및 대상체에서 표적 분자와 상호작용하도록 이들 화합물을 사용하는 방법이 개시된다. 일 측면은 세포의 표면 내 또는 표면 상에서 아스파르틸(아스파라기닐)β-하이드록실라아제(ASPH)의 발현 또는 촉매 활성을 조절하는 분자에 관한 것이다. 본 발명의 다른 측면은 세포 증식 장애 및 관련 질환을 진단, 개선 또는 치료하는 본원에 개시된 분자의 용도에 관한 것이다. 관련된 측면은 바이러스 활성 조절, 항고지혈증 제제로서, 그리고 혈전증 및 관련 심혈관 및 대사 장애를 개선 또는 치료하는 작용제로서 사용되는, 상기 화합물의 용도를 포함한다. Isotopically-stabilized tetronimide compounds comprising one or more deuterium atoms, derivatives, and intermediates, thereof, including methods for their synthesis, pharmaceutical compositions thereof, and methods of using these compounds to interact with target molecules in cell-free samples, cell- and tissue-based assays, animal models, and in a subject are disclosed. One aspect relates to molecules that modulate the expression or catalytic activity of aspartyl (asparaginyl) β-hydroxylase (ASPH) within or on the surface of a cell. Other aspects of the invention relate to use of the molecules disclosed herein to diagnose, ameliorate, or treat cell proliferation disorders and related diseases. Related aspects include uses of the compounds to modulate the activity of viruses, as anti-hyperlipidemia agents, and as agents to ameliorate or treat thrombosis and related cardiovascular and metabolic disorders.